Immediate Outcome of Mechanically Ventilated Neonate : One Year Experience in Neonatal Intensive Care Unit of Combined Military Hospital Dhaka (IAHS Medical Journal, 2022)
Background: A large number of neonates in intensive care unit require mechanical ventilation due to various disease conditions. There has been a dramatic fall in neonatal mortality in developed countries with the advent of mechanical ventilation. This study was carried out to see the immediate outcome of neonates who required mechanical ventilation.Materials and methods: This prospective observational study was carried out in Neonatal Intensive Care Unit, CMH Dhaka from January 2016 to December 2016. Neonates who required mechanical ventilation during the study period were enrolled in this study. During the time of mechanical ventilation neonates were followed up for any complication till discharge or death.Results: Total 30 neonates were enrolled in the study. Among them 22(73.3%) of the neonates were preterm and 8(26.7%) were term, 25(83.3%) having birth weight